The Role of TED-ED Animations in Enhancing the Speaking Fluency of Undergraduate ESL Learners in a Pakistani Setting - Rimsha Asghar; Asma Khan; Mahwish Farooq (University of Chitral Journal of Linguistics and Literature, 2023)
This mixed-method research study explored the role of integrating TED-ED animated video-based lessons on the speaking fluency of undergraduate ESL learners in a Pakistani setting. Grounded in Stephen Krashen’s Second Language Acquisition theory, this study investigated how comprehensible input, and affective factors impact second language acquisition. The researcher utilized an explanatory design, combining quantitative and qualitative methods to investigate the role of TED-ED video-based lessons in enhancing the speaking fluency of participants. The findings revealed a positive correlation between TED-ED video-based lessons and speaking fluency, with participants reporting increased confidence, fluency, and engagement. The study highlighted the significance of addressing affective factors, such as motivation and anxiety and creating a supportive learning environment to optimize second language acquisition. The incorporation of TED-ED video-based lessons provided valuable comprehensible input, authentic language exposure, and diverse topics, enriching the language-learning experience. The study’s implications extend beyond the Pakistani context, offering insights into ESL education globally, and emphasizing the importance of informed instructional design that integrates theoretical frameworks with practical pedagogical approaches. By leveraging multimedia resources like TED-ED video-based lessons, educators can cater to the diverse needs and preferences of ESL learners, enhancing language acquisition outcomes.